Traffic Accident Crime Due to Over Dimension Overload on Freight Transport Vehicles (Analysis of Decision Number: 49/PID. SUS/2022/PN-IDI) - Joko Muhar Irwansyah; Riza Zarzani (Yayasan Multidimensi Kreatif, 2024)
The problem of Over Dimension Over Loading (ODOL) in freight vehicles is the main issue that has a negative impact on traffic safety and road infrastructure. ODOL vehicles not only increase the risk of accidents, but also accelerate road damage and reduce the service life of infrastructure. This violation often occurs in the logistics sector, where business actors think that ODOL practices can improve transportation cost efficiency. Data from the Ministry of Defense shows that road damage caused by ODOL vehicles results in significant repair costs. Even though there are regulations that regulate the procedures for transporting goods, violations are still often committed. This study aims to examine the legal and enforcement aspects related to traffic accident crimes due to ODOL, with a focus on the analysis of case verdicts Number: 49/Pid.Sus/2022/Pn-Idi. The results of the study are expected to provide insight into the legal impact and the need for stricter enforcement of ODOL violations.